CLINICAL PROFILE OF PATIENTS WITH NORMAL CORONARY ANGIOGRAM - Hadi, Abdul; Ahmad, Farooq; Khan, Ikramullah; Iqbal, Muhammad Asif; Ashraf, Amber; Khan, Hafizurehman; Haq, Muhammad Rehanul; Shah, Sayyad Farhat Abbas; Hafizullah, Muhammad (Journal of Postgraduate Medical Institute, 2014)
Objective: To observe the clinical and bio-chemical profile of patients havingnormal coronary angiogram following an abnormal stress test. Methodology: This was a single center retrospective, descriptive study. Coronaryangiograms done from July 2009 to December 2011 were retrievedand reviewed for normal coronary arteries. Clinical and bio-chemical profileof the patients having normal coronary angiogram was retrieved from hospitalrecord. Patients, whose computerized data could not be retrieved fromdepartment database, were excluded from the study. Results: Out of 8425 angiograms reviewed, 816(9.7%) were having normalcoronary arteries. Mean age was 42±7.4 years. Females were 66.7%. Clinicaland biochemical profile for normal coronary angiograms was as follows:smokers 59%, family history of premature coronary artery disease 41%, hyperlipidemia18.5%and hypertension 14%. Diabetes was present only in 2.1%.Among females: 11% were current users of oral contraceptives pills, 3.4% werepost menopausal and 0.87% pregnant. Mean BMI was 25.4±5.2 and total cholesteroland triglyceride were 278±31mg/dl and 180±28mg/dl respectively. Conclusion: Normal coronary angiogram is infrequently observed in catheterizationlaboratories and mostly found in younger to middle aged females.Smoking is very common in such patients. Hyperlipidemia, hypertension, diabetesmellitus are not frequently present in these patients.